Big Data in Enterprise HR Systems: A Case Study on Workday API Integration - Nishitha Reddy Nalla, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
As cloud-based HR systems is being adopted by all organizations, the integration of Big Data has become indispensable in order to leverage workforce management and analytics. In this paper, we will provide a case study to integrate Big Data with Workday’s API to improve HR analytics and decision intelligence. While discussing the steps that can be taken to efficiently use Workday’s API and seamlessly integrate enterprise HR data, we explore these challenges around data extraction, transformation and real-time analytics. Security releases, data governance, AI-powered analysis, and future of people solutions are among the insights shared by the joint study.
Keywords: Big Data; Workday API; HR analytics; enterprise HR systems; workforce management; decision intelligence; cloud computing; AI-driven HR; predictive analytics; machine learning